Pengembangan Hasil Belajar Siswa Kelas II dalam Menggunakan Media Video Pembelajaran Di SD Ujung - Sri Devianti; Badruddin Kaddas; Rahmawati Rahmawati; Sri Hastati; Erwin Nurdiansyah; Ince Prabu Setiawan (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine the use of instructional video media (audio visual) to improve mathematics learning outcomes for second grade students of UPTD SDN 101 Inpres Ujung, especially in learning mathematics. This type of research is a type of quantitative method research in the element of classroom action research which consists of two cycles. This research was conducted at SDN 101 Inpres Ujung, Camba. Data collection techniques in this study used student activity observation sheets consisting of collecting data, test questions, and documentation. The data analysis technique uses student activities and student learning outcomes. The results showed that in the first cycle the students with complete learning outcomes in learning mathematics were 25 students or 80.64% and while the number of students who had not completed were 6 students or 19.35% with the value of student learning activities was 71.45 %. Furthermore, in the second cycle of students who completed were 29 students with a percentage of 93.54% and the number of students who did not complete was 2 people or equal to 6.45% with 83.87% student learning activities.